THE INFLUENCE OF MOTIVATION AND THE IMPLEMENTATION OF ACTIVE LEARNING TEAM QUIZ AS A LEARNING METHOD ON LEARNING OUTCOMES OF ECONOMICS STUDENTS IN SMA NEGERI I LUBUK ALUNG KABUPATEN PADANG PARIAMAN - Ripho Delzy Perkasa; Nuriza Dora (JURNAL TARBIYAH, 2022)
This research aims to reveal the effect of 1) Students who were taught by using active learning methods with quiz team learning and students who were taught economics through lecturing method in the SMA Negeri I Lubuk Alung, 2) Students with high motivation learned type of active learning methods of the type of quiz team would be higher learning outcomes than students who have high motivation to use the lecture method in the SMA Negeri I Lubuk Alung . 3) Students who have low motivation used active learning methods of the type of quiz, the team would have higher learning outcomes than students who have low motivation used the lecture methods in the SMA Negeri I Lubuk Alung. 4) The interaction between the application of active learning methods and the type of quiz team motivation towards learning outcomes of economics students in SMA Negeri I Lubuk Alung.This type of research was quasi-experimental research by using two-class research they were class control and experimental classes. The number of research samples from two classes was 63 students This type of data was primary data and secondary data. Learning motivation of data collection was done by spreading the. research questionnaire, while for the results of the research multiple-choice tests were provided at the end of learning. The data analysis techniques performed test data analysis requirements and test hypotheses with the two-way ANOVA. Research results indicated that: (1) There were the differences in learning outcomes of students who were taught economics with the type of active learning teaching methods quiz team than students who were taught using the lecture method in class XI IS SMA Negeri I Lubuk Alung (2) There was a  difference in student learning outcomes that have a high motivation on the type of active learning methods and student quiz team who have low motivation to use the lecture method in class XI IS SMA Negeri I Lubuk Alung 3) Students who have low motivation used active learning methods of the type of quiz, the team would higher learning outcomes than students who have low motivation used the lecture method in the SMA Negeri I Lubuk Alung (4) There was the interaction between the quiz active learning and motivation of team learning outcomes of students in class XI IS SMA Lubuk Alung.